MENINGKATKAN PERKEMBANGAN MOTORIK HALUS PADA ANAK MELALUI KOLASE DENGAN MEDIA DAUN KERING - Alisah Nur Azizah; Heri Yusuf Muslihin; Taopik Rahman (UHN I GUSTI BAGUS SUGRIWA DENPASAR, 2022)
Early childhood or preschoolers often have difficulty moving their fingers to perform activities such as tearing, cutting, drawing, folding, arranging, and filling in patterns by pasting small objects. This study aims to describe the fine motor skills of children and was conducted to determine the application of fine motor skills in children by doing collage activities. A form of ability that needs to be mastered by a child is physical motor skills, which are divided into two, namely fine motor and gross motor skills. Media that can develop it include using collage media because it is in accordance with the rules that must be owned by a child. The method used in this research is literature study or literature study, namely by collecting, processing and analyzing techniques from various sources or scientific journal references related to the problems studied. The results of this study prove that the use of collage media is very efficient and suitable for use in developing fine motor aspects in children so that children can coordinate between eyes and hands such as arranging, tearing, and sticking in collage activities.